Etiology of Food Addiction - Demet Gulec Oyekcin; Artuner Deveci (Psikiyatride Güncel Yaklaşımlar, 2012)
Food addiction is a new topic of focus in the scientific literature. Food intake might be concerned as food addiction in some cases, especially in obese cases and over-eaters. Addiction like behaviours are commonly observed mong these people. Recent animal, epidemiological, clinical and genetic studies partly shows the clinical validity of food addiction while the neurobiological studies focused on the similarity between the reward systems present in obesity and drug addiction. However some studies still emphasizes the differences between two. The aim of this article was to review clinical and biological aspects of etiological perspectives of food addiction via available clinical, preclinical and genetic studies.